Current trends in reduction or elimination of the aortic impulse during stent-graft deployment and balloon moulding during thoracic endovascular aortic repair. (9th August 2021) - Gottardi, Roman; Wyss, Thomas R; van den Berg, Jos C; Rylski, Bartosz; Berger, Tim; Schmidli, Juerg; Czerny, Martin
Abstract: : OBJECTIVES: A survey was performed to evaluate the methods used for reduction or elimination of the aortic impulse (REAI) to facilitate precise stent graft placement and balloon moulding during thoracic endovascular aortic repair (TEVAR). METHODS: A total of 127 physicians (1 per hospital) were contacted and asked to fill out a short, comprehensive questionnaire on an internet-based platform. RESULTS: Fifty physicians (39.4%) responded and completed the survey. Routine use of REAI for stent graft deployment is most frequently used in the ascending aorta and less frequently in the aortic arch and the descending aorta (86.4% vs 69.4% vs 56%). Some physicians based the decision of whether to use REAI on the type of stent graft in the respective location (13.6% vs 24.5% vs 24.0%). Stent-graft deployment without REAI, irrespective of the type of stent graft used, was never done in the ascending aorta (0.0%), in 3 centres in the aortic arch (6.1%) and in 10 centres in the descending aorta (20%). The REAI method most frequently used was dependent on the aortic segment (ascending aorta vs aortic arch vs descending aorta) rapid right ventricular pacing (90.9% vs 59.2% vs 28.0%), followed by pharmacological blood pressure reduction (13.6% vs 53.1% vs 64.0%) and venous inflow occlusion (13.6% vs 14.3% vs 4.0%), respectively. Tip capture and non-occlusive deployment systems were frequently quoted as reasons for not using REAI. CONCLUSIONS: REAI is the fundament for TEVAR in all thoracic aortic segments, with a decline in usage from proximal (ascending) to distal (descending). Rapid right ventricular pacing is the preferred REAI method used in TEVAR. Most procedures are performed with the patient under general anaesthesia. The types of stent grafts and moulding balloons used have an impact on the use or non-use of REAI. Abstract : Thoracic endovascular aortic repair (TEVAR) has become the therapy of choice in multiple thoracic aortic pathologies those involving the aortic arch and even the ascending aorta in selected patients.